A systematic review and meta-analysis of evidence-based practice and its associated factors among health professionals in Ethiopia - Tolesa Gemeda Gudeta; Ayana Benti Terefe; Girma Teferi Mengistu; Seboka Abebe Sori (BMC, 2024)
Abstract Background Evidence-based practice (EBP) entails utilizing the most up-to-date information to inform clinical decisions. Healthcare professionals at all levels are encouraged to integrate the latest research evidence to ensure high-quality care. In Ethiopia, there is a lack of comprehensive, nationally representative data on the prevalence of EBP among healthcare workers. This systematic review and meta-analysis aims to assess the overall prevalence of EBP and its associated factors among health professionals in Ethiopia. Methods This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The investigators searched electronic databases, including PubMed, Embase, Web of Science, Scopus, Cochrane Library, and Google Scholar, for studies published up to June 1, 2023. Two reviewers independently carried out the extraction of data and evaluation of study quality. We employed STATA version 14 for data synthesis and statistical analysis. The investigators used random-effects and fixed-effects models to calculate pooled odds ratios (ORs) and 95% confidence intervals (CIs) to determine the correlation between dependent and independent factors. The researchers conducted subgroup analysis to explore heterogeneity among the studies included and checked heterogeneity using the I2 statistic. The reviewers assessed publication bias using funnel plots and Egger's regression test. Results The initial search yielded 215 articles, of which 21 met the inclusion criteria. The pooled prevalence of good evidence-based practice among health professionals in Ethiopia was found to be 47.64 [95% CI: 41.33 to 53.96]. Having a masters and above educational status [pooled odds ratio (OR = 3.11; 95%CI: 1.945 to 4.95], good knowledge of EBP [OR: 2.44; 95%CI: 2.14, 2.78], training in EBP [OR = 2.30; 95% CI: 1.91, 2.77], availability of EBP guidelines [OR: 2.05; 95%CI: 1.60, 2.61], internet access [OR: 1.79; 95%CI:1.47, 2.18], availability of free time [OR: 2.05; 95%CI: 1.54, 2.72], presence of administrative support [OR: 1.89; 95%CI: 1.34, 2.67], clinical experience > 5 years [OR: 2.26; 95%CI: 1.54, 3.33], and positive attitude towards EBP [OR: 1.87; 95%CI: 1.53, 2.28] were significantly associated good evidence-based practice in Ethiopia. Conclusions Despite the importance of EBP in improving healthcare outcomes, its implementation among healthcare professionals in Ethiopia remains suboptimal. This study also identified modifiable factors associated with EBP adoption. Meanwhile, most of these factors are related to individuals and organizations. Strategies aimed at enhancing access to training and resources and fostering a supportive organizational culture are crucial for promoting EBP uptake and ultimately improving healthcare quality in Ethiopia.